Patterns of growth and development in the genus Homo - Thompson, J. L. (Jennifer Louise), 1961-; Krovitz, Gail E.; Nelson, Andrew John, 1960- (Cambridge studies in biological and evolutionary anthropology, 2003)
Our earliest human ancestors grew more like modern apes than present-day humans. When, how and why did our modern pattern evolve, therefore? This book, covering growth patterns in Plio-Pleistocene adults and juveniles, including Homo antecessor, provides a rich data source for future research.